2016
DOI: 10.1080/21655979.2016.1230571
|View full text |Cite
|
Sign up to set email alerts
|

New member of the hormone-sensitive lipase family from the permafrost microbial community

Abstract: Siberian permafrost is a unique environment inhabited with diverse groups of microorganisms. Among them, there are numerous producers of biotechnologically relevant enzymes including lipases and esterases. Recently, we have constructed a metagenomic library from a permafrost sample and identified in it several genes coding for potential lipolytic enzymes. In the current work, properties of the recombinant esterases obtained from this library are compared with the previously characterized lipase from Psychrobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This enzyme was isolated from a metagenomic library obtained from a Siberian permafrost sample. It demonstrated typical cold-adapted behavior, including a low-temperature optimum (30 • C) and low stability at elevated temperatures [22]. In the current study, we have shown that the thermal inactivation of PMGL3 is accompanied by the formation of oligomers and high molecular weight aggregates.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…This enzyme was isolated from a metagenomic library obtained from a Siberian permafrost sample. It demonstrated typical cold-adapted behavior, including a low-temperature optimum (30 • C) and low stability at elevated temperatures [22]. In the current study, we have shown that the thermal inactivation of PMGL3 is accompanied by the formation of oligomers and high molecular weight aggregates.…”
Section: Introductionsupporting
confidence: 52%
“…The mutant genes were constructed by two-step SOE (splicing with overlap extension)-PCR using wild-type PMGL3 gene as a template with Pfu DNA polymerase, and primers C49V for CCGAGGGCGTTTTGATCGAGC and C49Vrev GCTCGATCAAAACGCCCTCGG for the C49V mutant; C207F for CTGACCGGATTCTCGGCG and C207Frev CCGCCGAGAATCCGGTCAG for the C207F mutant. The resulting products were cloned into the pET32a vector, as described in [22]. Mutations were confirmed by DNA sequencing (Evrogen).…”
Section: Gene Cloning and Mutant Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several HSL-like enzymes have been reported from microbial sources, such as RmEstB from the thermophilic fungus Rhizomucor miehei [11], PMGL2 from a permafrost bacterium Psychrobacter cryohalolentis [12], and E25 HSL esterase from a surface sediment sample E505 collected from the South China Sea [13]. Even though there are many reported HSL-like esterase from psychrophilic microorganisms on heterologous expression and biochemical characterisation, there are few reports on HSL-like esterase specifically from psychrophilic yeast.…”
Section: Introductionmentioning
confidence: 99%
“…We have revealed different substrate specificities and various temperature optima of these enzymes demonstrating the broad spectrum of enzymatic activities which could be provided by the genome even of a single bacterium [29][30][31][32]. Screening of the metagenomic DNA library obtained from the permafrost-derived microcosm lead to the cloning of several genes coding for potential lipolytic enzymes [21,33]. Among them, a new esterase PMGL2 belonging to the hormone sensitive lipase (HSL, EC 3.1.1.79) family (family IV lipases) was produced and biochemically characterized [21].…”
Section: Introductionmentioning
confidence: 99%